2015
DOI: 10.1080/17458080.2015.1077533
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and photocatalytic activity of graphene-modified Ag2S composite

Abstract: This paper presents a novel visible-light photocatalyst, graphene-modified Ag 2 S (GR/Ag 2 S), prepared by a facile and effective hydrothermal method with AgNO 3 , thioacetamide and graphene oxide (GO) as the precursor. The catalytic activities of the GR/Ag 2 S hybrids with different GR content (2%, 4%, 6%) were evaluated by photocatalytic decolourisation of rhodamine B (RhB) solution under visible-light irradiation. The improved photocatalytic activity of GR/Ag 2 S composites compared with pure Ag 2 S is obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…It is found that the 2.4% CNT/Ag 2 S composite exhibits the highest apparent first-order reaction rate constant, k app , which is about 5.9 times higher than that for bare Ag 2 S nanoparticles. Compared with graphene-modified Ag 2 S, the visible-light-driven photocatalytic activity Ag 2 S can be much improved by the decoration of CNT [32].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is found that the 2.4% CNT/Ag 2 S composite exhibits the highest apparent first-order reaction rate constant, k app , which is about 5.9 times higher than that for bare Ag 2 S nanoparticles. Compared with graphene-modified Ag 2 S, the visible-light-driven photocatalytic activity Ag 2 S can be much improved by the decoration of CNT [32].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, for the bare Ag 2 S, the high recombination rate of photogenerated electron-hole (e − -h + ) pairs restricts its photocatalytic efficiency. As a result, many routes have been used to enhance the photocatalytic activity of Ag 2 S [28,29,30,31,32,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, for Ag 2 S/graphene, it was found that the performance of the photocatalyst depended on the relative amounts of semiconductor and graphene in the nanostructure. The authors have investigated samples with distinct graphene content (wt%: 2, 4, and 6), showing that in those conditions, the photodegradation of RhB, occurred most efficiently under visible-light irradiation in the presence of the sample 4 wt% in graphene [146].…”
Section: Application Of Carbon-based Semiconductor Nanostructures In ...mentioning
confidence: 99%
“…Silver sulphide (Ag 2 S) is another semiconductor that has shown promising photocatalytic activity [ 12 ]. However, Ag 2 S alone is not efficient for the degradation of pollutants, and in addition it has a relatively high cost [ 13 ].…”
Section: Introductionmentioning
confidence: 99%